Roles at crossroads: complexities and conflicts surrounding management accountants' roles based on evidence from the Sri Lankan context - Thenuja Sivabalachandran; Tharusha Gooneratne (AJAR (Asian Journal of Accounting Research), 2023)
Purpose – Drawing insights from finance and non-finance managers in Sri Lanka, this study unveils complexities and conflicts surrounding the roles of management accountants and the nature of role construction stemming from differing expectations of non-finance managers and external influences. Design/methodology/approach – This paper adopts the qualitative methodology and leans on role theory and new institutional sociology (NIS), as these dual theories complement each other and enable a holistic understanding of management accountants' roles, complexities and conflicts. Findings – The findings reveal that in fulfilling their roles on par with divisional goals, amid expectations of non-finance managers and external influences, management accountants face various complexities and conflicts. Furthermore, in navigating through their roles, understanding the operational realities of work organizations and business sectors and negotiating with non-finance managers is vital. Research limitations/implications – This research draws evidence from a selection of finance and non-finance managers. Thus the findings are not expected to be generalized to business firms in Sri Lanka. Practical implications – This paper offers practitioner insights into how management accountants could construct their roles in different organizational settings, balancing the expectations of non-finance managers and external influences. Originality/value – Despite its importance, complexities and conflicts surrounding management accountants' roles amid multiple influences have attracted scant research attention. Hence this paper is a noteworthy addition to the literature. Besides, using role theory and NIS in tandem although apt, has not been the focus of prior researchers in delving into this phenomenon.